PENGARUH KUALITAS PELAYANAN JASA TERHADAP KEPUASAN KONSUMEN PADA KARAOKE KELUARGA FAMILY BOX PANAM DI PEKANBARU - Maswir, Mulyadi (Eko dan Bisnis: Riau Economic and Business Review, 2021)
The place and location of this research was conducted at Karoke Keluarga Family Box Panam in Pekanbaru which is located on Jalan. HR. Soebrantas Pekanbaru. This study aims to determine the effect of service quality on consumer satisfaction Karoke Keluarga Family Box Panam Pekanbaru. In analyzing the data obtained from the object of this research using quantitative descriptive analysis. From the results of the multiple linear regression equation research, it is known that Y= 1.770 + 0.205X1 + 0.365X2 + 0.234X3 + 0.326X4 + 0.244X5, the conclusion is that service quality has a significant influence on the satisfaction of Karoke Family Family Box Panam Pekanbaru. The results of the discussion can be concluded that service quality affects the satisfaction of Karoke Family Family Box Panam Pekanbaru consumers, this is indicated by the influence of service quality indicators with consumer satisfaction. By knowing the value of R Square (RÂ²) of 0.575 or 57.5% . Adjusted R Square is used to determine the percentage influence of the independent variable (Tangible, Empathy, Reliability, Responsiveness, Assurance) on changes in the dependent variable (Consumer Satisfaction). The conclusion that can be drawn is the magnitude of the influence of the independent variable (Tangible, Empathy, Reliability, Responsiveness, Assurance) on the dependent variable (Consumer Satisfaction) is 57.5%, while the remaining 42.5% is influenced by other variables